Fabricated hadith: unraveling contradiction between society and scholar towards mutual agreement / Mohd Farhan Md Ariffin and Khadher Ahmad - Md Ariffin, Mohd Farhan; Ahmad, Khadher (Universiti Teknologi MARA, Perlis, 2016)
Hadith is the second source of Sharia in Islam. Hadith plays an essential role in Muslim life. Each saying leaned to Prophet Muhammad PBUH considered noble and followed by Muslims. Thus, appear irresponsible groups trying to ruin hadith authenticity. They are easily made up with something and using Prophet Muhammad name for personal interest. Consequently, fabricated saying or false hadith has been absorbed into Islamic tradition and religious scriptures that are believed by Muslims as well as used as an argument or in their daily practice. Regarding this, scholars have established various strict terms in order to purify Islamic teachings and restrict spreading of mawḍū'at (false, fictitious, fake hadith), so that the acceptable degree of hadith either be sahih or hasan. After proving the validity of hadith through narrators (sanad), they also need to study the content (matan) before it can be used as a source of law. On the same basis, this article tries to analyze the existence of fabricated hadith and views among scholars and civil society in Malaysia. As a result, researchers find out that scholars are strict in rejecting fabricated hadith compared to society seems to be more open to absorb all "hadith". Realizing this matter, researchers try to list a few important principles that must be understood together in order to eradicate the spread of fabricated hadith. Hopefully this article can provide exposure on the importance of authentic hadith to Muslims, especially among society in Malaysia.